2022
DOI: 10.3389/fphar.2022.989023
|View full text |Cite
|
Sign up to set email alerts
|

Methanolic Moringa oleifera leaf extract protects against epithelial barrier damage and enteric bacterial translocation in intestinal I/R: Possible role of caspase 3

Abstract: Background: Activation of caspase 3 has been implicated in the pathogenesis of I/R injury in various organs, but there is a paucity of data on its role in IIRI. Also, no reports were found on the beneficial role of methanolic Moringa oleifera leaf extract (MMOLE) in IIRI. This study investigated the involvement of caspase 3 in IIRI, and the impact of MMOLE in IIRI.Methods: Male Wistar rats were randomized into five groups; the sham-operated group that was sham-operated and received 0.5 ml of distilled water fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 53 publications
0
10
0
1
Order By: Relevance
“…The abdomen was shaved and washed with normal saline solution and a sterile eye-field was placed over the operative site. As described by Afolabi et al, [17] midline incision on the abdomen the cecum and terminal ileum were mobilized and the ileocaecal junction identified. A 5 cm segment of the terminal ileum 5 cm from the ileo-cecal junction (ICJ) was twisted 360 0 clockwise along the mesentery (to cause ischemia) and anchored to the anterior abdominal wall with 2-0 chromic suture.…”
Section: Experimental Induction Of Intestinal Ischemia Reperfusion In...mentioning
confidence: 99%
See 1 more Smart Citation
“…The abdomen was shaved and washed with normal saline solution and a sterile eye-field was placed over the operative site. As described by Afolabi et al, [17] midline incision on the abdomen the cecum and terminal ileum were mobilized and the ileocaecal junction identified. A 5 cm segment of the terminal ileum 5 cm from the ileo-cecal junction (ICJ) was twisted 360 0 clockwise along the mesentery (to cause ischemia) and anchored to the anterior abdominal wall with 2-0 chromic suture.…”
Section: Experimental Induction Of Intestinal Ischemia Reperfusion In...mentioning
confidence: 99%
“…# Values differ significantly from reperfusion injury (#p < 0.05, ##p < 0.01, ### p < 0.001).▶Fig. 2 Bar chart showing the effect of reperfusion injury and cysteamine on the intestinal tissue level of GSH and GPx using ellman reagents as described by Oladele[17]. Values were expressed as mean ± SEM, for eight rat per group.…”
mentioning
confidence: 99%
“…For example, in the SI, superior mesenteric artery clamping model is currently used to evaluate IIRI, requiring one animal for each sample and study time. 1529 The same situation occurs in the field of experimental colitis, where old and recent scientific articles use one animal in each LI sample collection. 3037 For the reasons mentioned above, it is a challenge to develop models that enable reducing the number of animals involved in these studies.…”
Section: Introductionmentioning
confidence: 87%
“…Among experimental studies focused on gastrointestinal diseases found in the literature, IIRI- and 2,4,6-trinitrobenzenesulfonic acid (TNBS)-induced colitis in rats appears as a current model used by many authors and research groups around the world. 2037 For this reason, we selected these two relevant pathologies to evaluate the experimental BK procedure in an intestinal injury scenario. IIRI was used for simulating a model of intestinal intussusception, strangulated hernia or intestinal transplantation.…”
Section: Methodsmentioning
confidence: 99%
“…De los estudios experimentales focalizados en patología de intestino delgado la IIR es un modelo de interés en la actualidad. (91)(92)(93)(94)(95)(96)(97)(98)(99)(100) Materiales y métodos: Se emplearon ratas Wistar hembras (peso 221 ± 13 gr). A las mismas se les proporcionó agua y alimento a demanda previo al acto quirúrgico.…”
Section: Bk Para El Estudio De La Iir Intestinalunclassified